SAT0134 Mortality and multiple causes of death in rheumatoidarthritis patients. results from a large population-based cohort in the venetoregion, 2010-2015. (12th June 2018) - Ometto, F.; Fedeli, U.; Botsios, C.; Schievano, E.; Corti, M. C.; Punzi, L.
Abstract : Background: Mortality rates in patients with rheumatoid arthritis (RA) are 1.5-1.6 fold higher than in the general population 1, 2 . No recent data on mortality in large cohorts of RA patients in Italy are available. Objectives: The aim of this study was to assess standardized mortality ratios (SMRs) and multiple causes of death in RA subjects living in the Veneto Region between 2010 and 2015. Methods: We identified in the electronic archive of the Veneto Region a cohort of patients aged 20-89 years who were exempt from copayment for RA in January 2010, and linked them with the archive of causes of deaths of the period 2010-2015. The record-linkage was performed on previously anonymized records. In the Veneto Region a copy of all death certificates is transmitted to the Regional Epidemiology Service for coding of causes of death according to the International Classification of Diseases, 10th Edition. Each subject was followed from 1st January 2010 either until death, or 90 years of age, or 31st December 2015, whichever came first. In the Veneto Region, the archive of causes of death include all diseases mentioned in the death certificate, and the selection of the underlying cause of death (UCOD) is performed by means of the Automated Classification of Medical Entities, a computer program developed by the US National Center for Health Statistics. SMRs with 95% confidence intervals, were computed as the ratios between deaths observed in the cohort, and those expected according to age- and gender-specific regional mortality rates. Results: Overall 16, 098 residents diagnosed with RA and aged 20-89 years were enrolled in the cohort. Follow-up was complete for above 99% of study subjects. The overall follow-up amounted to 88, 599 person-years, with 2, 142 registered decedents. The most common causes of death were circulatory diseases (36.6%), neoplasms (24.2%), and respiratory diseases (8.3%). SMR in RA subjects was 1.42 (1.36-1.48).Mortality was significantly increased from circulatory, respiratory, digestive, infectious, hematological diseases and falls (figure 1). Mortality fromneoplasms was similar to that expected based on rates from the generalpopulation. RA was selected as the underlying cause of death in 6.1% of all deaths in the cohort and was mentioned in 25.4% of death certificates. Conclusions: Overall, a 42% excess risk of death could be observed among patients with RA in the Veneto Region.These data confirm results from previous studies in large cohorts of RAsubjects [1, 2]. References: [1] Sokka T, Abelson B, Pincus T. Mortality in rheumatoid arthritis: 2008 update. Clin Exp Rheumatol 2008;26(Suppl 51):S35-61. [2] van den Hoek J, Boshuize HC, Roorda LD, et al. Mortality in patients with rheumatoid arthritis: a 15-year prospective cohort study. Rheumatol Int 2017;37:487-493. Disclosure of Interest: None declared